PENGEMBANGAN APLIKASI EDUKASI ANIMASI 3D HURUF HIJAIYAH BERBASIS ANDROID - Nawassyarif; Esabella, Shinta; Syukur, Muhammad (POLITEKNIK NEGERI JAKARTA, 2022)
The utilisation of the proper media is a solution to resolving delays in understanding the subject matter. Together in an all digitalized era, it is the Alpha generation children who need to be educated according to the minimum standards of the expected lessons. Knowing the letters of guidance is the primary step to proficiency in reading the Koran, so it is necessary to provide media products in the form of 3D animation to make it easier for Muslim children to learn the letters of hijaiyah. The basis of the research was found through qualitative methods and the development of this application using the Rapid Application Development or RAD method not as it abbreviates the time but moreover makes the program quality in structured coding because the RAD method has repetition in minimising Debug. In software development, a testing method is used, specifically dark box testing, a test method that can show the functionality of a well-developed UI/UX system in a 3D animation application for learning hijiayah letters. Hijaiyah letter 3D animation technology which is programmed for the Android platform to make it easier to learn hijaiyah letters for Muslim children because 3D animation educational applications learning hijaiyah letters can add insight to Muslim children.